Physico-mechanical properties of cross-laminated timber manufactured from Acacia mangium Willd. wood - Mohd Yusof, Norwahyuni (2018)
Cross Laminated Timber (CLT) using mass timber has becoming more popular due to various sustainability advantages and benefits, notably the speed and ease with which CLT buildings can be constructed. This study evaluates the bond integrity and strength properties of CLT made from tropical Acacia mangium Willd. wood. In the preliminary study (Part 1), the bonding integrity of the CLT were assessed by determining the surface wettability using contact angle method, percent delamination and shear strength upon block shear test of CLT. The evaluation of bonding characteristics was done on two types of adhesive (PUR and PRF), three pressing pressures (0.9N/mm², 1.2 N/mm², 1.5N/mm²), and three adhesive spread rates (150g/m², 200g/m², 250g/m²). Two types of two-layer block shear samples were prepared with grain orientation parallel (denoted as parallel laminated block) and perpendicular (denoted as cross laminated block) to each other. The shear performance was conducted on two loading directions: parallel to end grain and perpendicular to the grain of the first layer. Additionally, delamination tests were performed on three-layer CLT to assess the durability of bonds in severe environmental conditions. Tests were conducted according to EN391 (Delamination test) and EN392 (Block shear test). The ANOVA in preliminary study shows that among the parameters studied (adhesive types, spread rate, pressing pressure and loading direction), only adhesive types have significant effect on both the extent of delamination and shear bond strength of the blocks. Whilst both adhesive spread rate and loading direction have a marked influence on the shear strength but not on percent delamination, irrespective of adhesive types. Loading direction appears to greatly influence the shear bond values and wood failure percentage. The effects was more pronounced in the parallel laminated block rather than cross laminated block. The results also revealed that PRF-bonded laminated block experienced lower percent delamination (50%) as compared to that bonded with one component PUR (80%). PRF was found to be a more superior adhesive than PUR irrespective of clamping pressure and loading direction. The superior performance of PRF can be attributed to strong chemical bonding, stable and better gap-filling properties. Based on the optimum parameters in preliminary study, the larger sized (Part 2) were produced with (1000 (l) ×280 (w) ×54(t) mm), three-layer CLT were fabricated using Acacia mangium lumbers and its physical, mechanical and thermal properties were evaluated. Two types of adhesives were used: one-component polyurethane (PUR) and phenol resorcinol formaldehyde (PRF) as binders. Using a spread rate of 250g/m², the CLT was pressed at 1.5N/mm² for 1 hour 30 minutes. After conditioning, the CLT was tested according to European Standard, EN408 and prEN16351. Based on physical, mechanical and thermal properties, Acacia mangium can be converted to structural grade CLT provided that the maximum bending load is improved. CLT panels with PRF adhesive is more resistant in water compared to those bonded with PUR. The MOE and MOR of PRF-bonded CLT is superior than the PURbonded CLT higher in four- point bending, shear in bending and compression parallel to the grain. Different failure modes were observed in Acacia mangium CLT: rolling shear, glueline failure, tension, shearing and crushing. In thermal properties (thermogravimetric analysis and dynamic mechanical analysis), PRF imparts greater stability to Acacia mangium CLT compared to PUR.